PENGEMBANGAN MATERI PEMBELAJARAN SENI MUSIK BERBASIS SENI BUDAYA BERKONTEKS KREATIF, KECAKAPAN HIDUP, DAN MENYENANGKAN BAGI SISWA SD/MI (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2009)
Education Unit Level Curriculum (KTSP) in Elementary School / MI, the level ofimplementation still meet many difficulties and obstacles experienced by theteachers. The research objective is to find information to develop teaching materialsbased music arts and culture for elementary school children / MI that can supportthe development of students' creative thinking, provide supplies to the students lifeskills, and create a pleasant learning atmosphere (joyful learning). Based on the dataobtained, it can be concluded that the current primary school teachers / MI are stillexperiencing difficulties and obstacles in learning the art of music. Difficulties andobstacles are: (1) the ability to translate the contents of the education unit levelcurriculum (KTSP) competency-based music, (2) the ability to optimize your child'smusic potential, (3) apply the method, (4) use of education tools and media (5)utilisation of the potential of cultural and natural environments around, and (6)develop an evaluation form. In this study developed a textbook model of musicteaching materials that are expected to be implemented at the same time teachersare able to stimulate and motivate teachers to develop further music learning.Suggestions proposed is that the institutions associated with the development oflearning in primary schools can develop training programs, development ofsourcebook and textbook which considers the potential of art, culture, and the needsof teachers.Kata kunci : seni budaya, kreatif, kecakapan hidup dan menyenangkan